Friction passion brands in the age of disruption - Rosenblum, Jeff; Berg, Jordan (Tantor Audio, 2019)
Every industry around the globe is being completely disrupted. Stalwart brands are losing market share to upstarts that capture our collective consciousness. Trillions of dollars are at stake. Brands know a new approach is needed. But most don't realize the strategic underpinnings need to change. Great brands are no longer built through interruptive advertisements. Friction argues that brands don't simply need clever messages or new, shiny technologies. They need a fundamental change in strategy. Friction provides a system for embracing transparency, engaging audiences, creating evangelists, and unleashing unprecedented growth. The authors of Friction have worked on some of the industry's most innovative assignments for the world's most successful brands. This groundbreaking book reveals how corporations can divorce themselves from legacy business models to create a passion brand. A brand that breaks its addiction to traditional advertising. A brand that empowers its customers. A brand that dominates the competition.
Online resource; title from title details screen (OverDrive, viewed August 23, 2019)
Keywords: Branding (Marketing); Advertising -- Brand name products; Product management; Stratégie de marque; Produits de marque; Publicité; Produits commerciaux; Gestion; branding; BUSINESS & ECONOMICS; New Business Enterprises; Advertising; Brand name products; Downloadable audio books; Audiobooks; Livres audio